2004
DOI: 10.1103/physrevlett.92.165002
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigm for the Isotope Scaling of Plasma Transport Paradox

Abstract: Most tokamak experimental results [Nucl. Fusion 33, 1205 (1993)]] and basic physics experiments [Phys. Rev. Lett. 89, 095001 (2002)]] in the Columbia Linear Machine indicate dependence of the ion thermal conductivity on the isotopic mass close to chi( perpendicular ) approximately A(-0.5)(i), i.e., inverse gyro-Bohm. This is in stark contradiction to most present theoretical models predicting Bohm (A(0)(i)) or gyro-Bohm (A(0.5)(i)) scaling. A series of experiments designed to explore the physics basis of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…3 Plasma experiments in a simple linear configuration have been revisited recently for quantitative understandings of the structural formation mechanism by turbulence. [4][5][6][7][8][9][10][11][12] A density gradient drives the drift wave turbulence in these plasmas. Two-dimensional measurements reveal the feature of turbulent structures 13,14 and their formation mechanisms by nonlinear mode coupling.…”
Section: Introductionmentioning
confidence: 99%
“…3 Plasma experiments in a simple linear configuration have been revisited recently for quantitative understandings of the structural formation mechanism by turbulence. [4][5][6][7][8][9][10][11][12] A density gradient drives the drift wave turbulence in these plasmas. Two-dimensional measurements reveal the feature of turbulent structures 13,14 and their formation mechanisms by nonlinear mode coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an advance in the study of the nonlinear interaction between drift wave turbulence and meso-scale structures such as zonal flows and streamers [1,2], and experiments in linear plasma devices have been in progress [3][4][5][6][7][8][9][10]. In these studies, complex wave patterns in poloidal direction have been observed (see also reports from toroidal plasma experiments, e.g., [11][12][13][14]).…”
Section: Introductionmentioning
confidence: 90%
“…Plasma experiments in a simple linear configuration have been revisited recently for quantitative understandings of the structural formation mechanism by turbulence [6][7][8][9][10][11][12][13][14]. Drift wave turbulence is driven by the density gradient, which is universal in confined plasmas, and has been observed in linear configurations [7,8,15].…”
Section: Introductionmentioning
confidence: 99%